(3GdLjhdhLjG GdYGeIs - (3UhGdMI, Mce YHO GdLHGQ eUWais ((3YeGf, GdCQOf (B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY hGdWHGYI,s, 2005)
(3fHPI Yde GdLjhdhLjG hchcH GdCQV(B.s
(3bGFeI HGdeUWdMGJ (B: (3U(B. 419-452.s
(3cTGa (B: (3U(B. 417-418.s
(3HHdjhLQGajI (B: (3U(B. 416.s
(3GdSfGfj(B.s
1.
Keywords: (3GdLjhdhLjGs